1988
DOI: 10.3164/jcbn.5.135
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Nature of β-Nerve Growth Factor (NGF)-Like Immunoreactive Substance(s) in Mouse Plasma

Abstract: A highly sensitive two-site enzyme immunoassay system macromolecule(s) through disulfide linkage(s) in mouse plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This assay provided a reliable determination of NGF levels in serum and it became clear that in rat and mouse serum there is less than 5 ng of NGF per ml, in agreement with results obtained from bioassays of NGF activity. Up until now the only clear case in which the presence of NGF has been detected in serum is in mouse where most of it is probably derived from the extreme amounts of NGF found in the submandibular gland (Aloe et al, 1986;Shinoda et al, 1988). Shinoda et al (1988), using the sensitive two-site EIA found serum levels of NGF in the male mouse to be 0.07 ng/ml and for the female mouse 0.01 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assay provided a reliable determination of NGF levels in serum and it became clear that in rat and mouse serum there is less than 5 ng of NGF per ml, in agreement with results obtained from bioassays of NGF activity. Up until now the only clear case in which the presence of NGF has been detected in serum is in mouse where most of it is probably derived from the extreme amounts of NGF found in the submandibular gland (Aloe et al, 1986;Shinoda et al, 1988). Shinoda et al (1988), using the sensitive two-site EIA found serum levels of NGF in the male mouse to be 0.07 ng/ml and for the female mouse 0.01 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that high molecular weight species that bind 1251-labelled mouse PNGF exist in human serum. Moreover, it has been suggested that NGF may circulate in plasma complexed through disulfide linkage with macromolecular components (Shinoda et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…As a2M is abundant in serum (1.5-4.2 mg in human sera) and NGF is in low concentration in the body, it is likely that NGF released into the blood stream is completely absorbed by a,M. Only in mice NGF is detected in serum or plasma by radioimmunoassay (Aloe et al, 1986;Lakshmanan, 1986) or EIA (Shinoda et al, 1988). In this case, the circulating factor is considered to be derived from the submaxillary gland, which gland in mice contains an extremely large amount of NGF.…”
Section: Introductionmentioning
confidence: 99%